The Nexus Between Economic Demography and Carbon Emission: A Case Study in South American Region - Yahya Mahda Vikia; Valeriana Sekar Adhianti Wibowo; Faizal Maulana; Dwi Rahmayani (Journal of Economics Research and Social Sciences, 2023)
One of the world community's current challenges is determining how to achieve the SDGs goals on environmental quality before 2030. This study aims to determine how the massive population and economic growth affect the emission of carbon dioxide (CO2) gas in the six South American countries with the largest population and use the Environmental Kuznets Curve (EKC) hypothesis approach. The data used is panel data from 2011 to 2021 in six countries based on the average population of the largest population over 11 years in South America. The results of the study explain that the total population has a significant positive effect on CO2 emissions. In addition, trade openness through imports has a significant positive effect and this study was unable to validate the Environmental Kuznets Curve (EKC) hypothesis in six South American countries from 2011 to 2021.